Desarrollo, cooperación y post-desarrollo en Timor Oriental - McGregor, Andrew (Revista Española de Desarrollo y Cooperación, 2023)
Post-development theories have had a considerable success in their challenge to our ways of thinking the development, but their impact has been a lot lower in the practical environment. This article tries to explore the opportunities that the post-development ideas bring to the existing development system in Oriental Timor.